Pancreas-Preserving Duodenal Resections with Bile and Pancreatic Duct Replantation for Duodenal Dystrophy. Two Case Reports - Egorov, Viacheslav Ivanovich; Butkevich, Alexander Cezarevich; Sazhin, Alexander Viacheslavovich; Yashina, Nina Ivanovna; Bogdanov, Sergei Nikolaievich (JOP. Journal of the Pancreas, 2010)
Context Duodenal dystrophy is a rare disease, characterized by the chronic inflammation of the aberrant pancreatic tissue in the duodenal wall. Case reports Two middle-aged men were admitted with upper abdominal pain of several months duration, periodic nausea and vomiting after meals, intermittent jaundice and weight loss. A diagnosis of cystic dystrophy of the vertical part of the duodenum without chronic inflammation of the orthotopic pancreas was established in both cases by multi-detector computed tomography, magnetic resonance imaging and endosonography. Both patients were successfully treated by two modifications of pancreas-preserving duodenal resections with reimplantation of the bile and pancreatic ducts into the neoduodenum. Conclusion These cases are a good example of a pancreas-preserving approach to duodenal dystrophy treatment and can be an alternative to the Whipple procedure in cases of mild changes of the orthotopic gland. Image: Resected specimen of the second part of the duodenum.